Art to enhance consumer engagement in the luxury fashion domain. Issue 3 (7th April 2020) - Grassi, Alessia
Abstract : Purpose: This paper explores an opportunity for luxury fashion brands to strengthen their engagement with consumers through the arts and without undermining the exclusivity of the luxury product. Design/methodology/approach: This paper is based on an interpretive qualitative approach aiming to specifically investigate Fondazione Prada – a contemporary art gallery owned and managed by the fashion brand Prada. Data were collected through semi-structured interviews and a focus group implemented with the "mystery shopper" technique. Template analysis was used to analyse the data. Findings: Fondazione Prada has the potential for a deep engagement, but specific lack of dialogue and interaction needs to be addressed. Learning from and sharing values with the public through a two-way peer conversation elicited by contemporary art will benefit both the foundation and the fashion brand, in generating value as the result of a spillover effect. Thus, a significant competitive advantage might be gained. Originality/value: This paper extends work on consumer brand engagement in physical and non-commercial "brand's places", by evaluating the engagement provided by contemporary art foundations owned by luxury fashion brands. By leveraging the engaging nature of contemporary art, luxury fashion brands could provide an inclusive and engaging experience without undermining the characteristic of exclusivity of the luxury product and hence, gain a significant competitive advantage for the brand.